How to read and understand the Psalms - Waltke, Bruce K.; Zaspel, Fred G.; Ferguson, Sinclair B. (Wheaton, Illinois : : Crossway, 2023)
"In How to Read and Understand the Psalms, Bruce K. Waltke and Fred G. Zaspel give readers tools to learn how to properly interpret and internalize the Psalms. Developed primarily from decades of lectures by Waltke, they explain the various types of psalms, Hebrew poetry, rhetorical techniques, and more. Armed with these tools, readers will discover how the 150 psalms can further fuel their knowledge and love of God"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher ; resource not viewed
Keywords: Bible. -- Criticism, interpretation, etc; Bible. Psalms--Criticism, interpretation, etc